Addictive Behaviors: New Readings on Etiology, Prevention, and Treatment. 2009
DOI: 10.1037/11855-023
|View full text |Cite
|
Sign up to set email alerts
|

Preventing substance abuse in American Indian and Alaska native youth: Promising strategies for healthier communities.

Abstract: It has had profoundly harmful consequences on both individual and societal levels, and it is widely believed that few Indian families remain tmaffected, either directly or indirectly. The historical and political context surrounding alcohol use among American Indians and Alaska Natives is far too complex to address in the scope of this chapter (for a more in-depth discussion of this topic, see E. H. Hawkins & Blume, 2002). Although many communities have experienced social and cultural devastation that can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 84 publications
0
60
1
2
Order By: Relevance
“…In one study, spiritual/traditional practices were shown to be a protective factor against suicide among American Indians (Garroutte et al, 2003). However, other research in this area that assessed traditions and culture as a strength has had conflicting results, with identity and self-concept and participation in traditions sometimes being associated with decreased (Thurman & Green, 1997) and sometimes increased rates of alcohol or substance use (Hawkins et al, 2004;Mail, HeurtinRoberts, Martin, & Howard, 2002;Petoskey, Van Stelle, & De Jong, 1998;Yu, Stiffman, & Freedenthal, 2005).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In one study, spiritual/traditional practices were shown to be a protective factor against suicide among American Indians (Garroutte et al, 2003). However, other research in this area that assessed traditions and culture as a strength has had conflicting results, with identity and self-concept and participation in traditions sometimes being associated with decreased (Thurman & Green, 1997) and sometimes increased rates of alcohol or substance use (Hawkins et al, 2004;Mail, HeurtinRoberts, Martin, & Howard, 2002;Petoskey, Van Stelle, & De Jong, 1998;Yu, Stiffman, & Freedenthal, 2005).…”
mentioning
confidence: 94%
“…This is because strength characteristics develop within a complex mixture, with the presence of positive behaviors not necessarily being linearly associated with the absence of negative behavior (Hawkins et al, 2004;Mitchell & Beals, 1997). However, almost universally, familial strengths appear as a significant factor in both the research and theoretical literature (e.g., Bearinger et al, 2005;Cummins, Ireland, Resnick, & Blum, 1999;Stubben, 1997).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…El consumo de alcohol en jóvenes, como fenóme-no, resulta bastante complejo de predecir debido a la multiplicidad de factores asociados al mismo, entre ellos los estados afectivos, la motivación, los procesos conductuales de ingesta, el balance decisional (Flórez-Alarcón, Botero & Moreno, 2005;Flórez-Alarcón, 2007), el género, la edad, el nivel socio-económico, los antecedentes familiares de ingesta, el patrón de consumo de pares y amigos (Rhodes & Jason, 1990;Carmona & Chávez, 1991;Donaldson, Graham, Piccinin & Hansen (1995); Stice, Myers & Brown, 1998;Ouellette, Gerrard, Gibbons & Reis-Bergan, 1999;James, 2003;Guerrero, 2003;Uruk & Demir, 2003;Hawkins, Cummins & Marlatt, 2004;Londoño, 2007;Londoño, Valencia, Hernández & León, 2007), la capacidad para resistir la presión del grupo dirigida a promover el consumo, el rendimiento escolar y la migración del país (Carvajal & Andrade, 2005).…”
Section: Introductionunclassified
“…Ergenler, yaşamla nasıl başa çıkacaklarını öğrenecekleri yeni deneyimlerle daha fazla ilgileneceklerdir. Bu açıdan bakıldığında davranış değişikleri "iyileşme ve düzelme"den çok bir "keşif yolculuğu"na dönüşür (Hawkins, Cummins, Marlatt, 2004).…”
unclassified